The Question of Technology Reloaded: Searching for the Limits of the Machine (KULT_online, 2010)
Denken bis an die Grenzen der Maschine (Thinking to the Limits of the Machine) consists of interviews with the French philosopher and media theorist Bernard Stiegler, which were first broadcast on France Culture. Edited by Erich Hörl, this collection provides insight into Stiegler’s attempt to rethink the question of technology. In so doing, the interviews touch upon subjects much discussed in this field: from the relation between man and machine to his technological condition to the technicity of consciousness. Stiegler’s concept extends – or rather, corrects – this set of approaches with his theory of "industrielle Zeitobjekte" (p. 11, 'industrial time objects'), thus coming to an "Analytik der Gegenwart" (p. 9, 'analytics of the present') and, as announced in the blurb, a new criticism of programme industries and technosciences. This ambitious aim, however, fails because of the inevitable redundancies and edits in terms of content which result from the texts being (radio-)interviews – with all their formal (dis-)advantages.